PERAN PERCEIVED VALUE DALAM MEMEDIASI PENGARUH GREEN MARKETING TERHADAP PURCHASE INTENTION - I Gusti Ayu Tirtayani; Ni Wayan Ekawati; Ni Nyoman Kerti Yasa (Forum Manajemen STIMI Handayani Denpasar, 2016)
Green marketing refers to the satisfaction of the needs, wants and desiresof customers in relation to the maintenance and preservation of the environment.The benefits obtained with the green marketing is to produce products that use rawmaterials that are environmentally friendly (green product). This research wasconducted in the Carrefour shopping center and Hardy’s. The number of samplestaken are 100 responden, using purposive sampling and accidental sampling. Theanalysis technique used is path analysis. Based on the results of research conductedfound that green marketing affect positively and significantly related to perceivedvalue, green marketing affect positively and significantly related to purchaseintention, perceived value affect positively and significantly related to purchaseintention, and perceived value to mediated a positive and significant effect of greenmarketing to the purchase intention.